Fiscal competition and reality: A time series approach - Zsolt Becsi (Federal Reserve Bank of Atlanta, 1998)
Strategic interjurisdictional behavior and the interaction over time of the mean and dispersion of average tax rates across states are analyzed in a vector autoregression model. Variance decompositions reveal that fiscal competition explains roughly one-third of the time variation of state and local taxes. Impulse response functions identify the type of fiscal competition and the characteristics of leaders and followers. Local tax dynamics agree with Wildasin's (1988) results on expenditure competition with significant short- and medium-run effects but insignificant long-run effects. State tax dynamics conform to tax export competition with significant effects occurring over a relatively short time.
Keywords: 330; State finance; Time-series analysis